The fear and risk of community falls in patients following an intensive care admission: An exploratory cohort study. Issue 2 (March 2020) - Parry, Selina; Denehy, Linda; Granger, Catherine; McGinley, Jennifer; Files, D Clark; Berry, Michael; Dhar, Sanjay; Bakhru, Rita; Larkin, Jane; Puthucheary, Zudin; Clark, Ross; Morris, Peter
Abstract: Background: Muscle weakness and impairments in physical functioning are well-recognised sequelae after critical illness. Whether individuals have a higher risk of community falls and a fear of falling has not been examined amongst individuals after critical illness. Objectives: The objective of this study was to explore the prevalence of falls, fear of falling, and fall risk in intensive care unit (ICU) survivors over a 6-month period after hospital discharge. Methods: This was a nested exploratory study within a medical ICU. Fall prevalence was measured in line with established guidelines over 6 months after ICU discharge. Fear of falling and prediction of fall risk were assessed at 2, 4, and 6 months after discharge. Results: Twelve individuals were included. Half of the cohort (n = 6) had at least one fall, with one-third sustaining more than one fall. There were 17 falls reported across the six individuals. Injuries requiring medical intervention were reported with five falls. Almost one-third were classified as 'moderate' to 'severe' injurious falls. Loss of balance and fatigue were reported as the main contributors to the falls. All individuals who had a fall reported a severe fear of falling at 2 months. Individuals classified as having 'moderate' to 'high' risk of falls at 2 months were more likely to have at least one fall. Conclusions: This study suggests that ICU survivors may have a high fall risk, fear of falling, and fall prevalence, which can result in significant injury.